2015
DOI: 10.1136/bcr-2015-210906
|View full text |Cite
|
Sign up to set email alerts
|

Benign mixed tumour of the breast and breast skin, two cases with diagnostic difficulties

Abstract: SUMMARYWe present two cases of pleomorphic adenoma, one that developed in the breast parenchyma and the other in the breast skin, with their histopathological differential diagnosis. BACKGROUND

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
(28 reference statements)
0
5
0
Order By: Relevance
“…4 Mainly occurs in the head, face, neck, often involving nose, cheek, upper lip, and other parts; occasionally occurs in the trunk, limbs, perineum, and other parts. 5,6 Histopathologic manifestations are composed of epithelial components (various cellular components such as eccrine, apocrine, sebaceous, and hair) and interstitial components (cartilage-like or mucus-like matrix). Skin mixed tumor is a mass with clear boundary under low magnification.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Mainly occurs in the head, face, neck, often involving nose, cheek, upper lip, and other parts; occasionally occurs in the trunk, limbs, perineum, and other parts. 5,6 Histopathologic manifestations are composed of epithelial components (various cellular components such as eccrine, apocrine, sebaceous, and hair) and interstitial components (cartilage-like or mucus-like matrix). Skin mixed tumor is a mass with clear boundary under low magnification.…”
Section: Discussionmentioning
confidence: 99%
“…It is more common in men than women and more common in people between the ages of 20 and 40 4. Mainly occurs in the head, face, neck, often involving nose, cheek, upper lip, and other parts; occasionally occurs in the trunk, limbs, perineum, and other parts 5,6…”
Section: Discussionmentioning
confidence: 99%
“…A comparison of the staining qualities of the stroma in PA to those of mucinous carcinoma has shown that the mucin in PA will be lost on alcian blue with hyaluronidase treatment, whereas it will be preserved in mucinous carcinoma. This feature may be used in the distinction of the two entities 21 …”
Section: Discussion/conclusionmentioning
confidence: 99%
“…This feature may be used in the distinction of the two entities. 21 Other diagnoses in the differential included metaplastic carcinoma, fibroepithelial neoplasms of the breast, papillomas, and other salivary gland-type neoplasms.…”
Section: Discussion/conclusionmentioning
confidence: 99%
See 1 more Smart Citation